2007
DOI: 10.1242/dev.001016
|View full text |Cite
|
Sign up to set email alerts
|

The AP2 transcription factors DORNRÖSCHEN and DORNRÖSCHEN-LIKE redundantly controlArabidopsisembryo patterning via interaction with PHAVOLUTA

Abstract: DORNRÖSCHEN (DRN) (also known as ENHANCER OF SHOOT REGENERATION1; ESR1)and DRN-LIKE (DRNL; also known as ESR2) are two linked paralogues encoding AP2 domain-containing proteins. drn mutants show embryo cell patterning defects and, similarly to drnl mutants, disrupt cotyledon development at incomplete penetrance. drn drnl double mutants with weak or strong drnl alleles show more highly penetrant and extreme phenotypes, including a pin-like embryo without cotyledons, confirming a high degree of functional redund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
207
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(224 citation statements)
references
References 61 publications
12
207
0
3
Order By: Relevance
“…Chandler et al (2007) found that the HD-ZIPIII protein PHAVOLUTA interacts with the AP2 family DORNRÖ SCHEN and DORNRÖ SCHEN-LIKE transcription factors. Moreover, dornröschen dornröschenlike double mutants fail to make cotyledons indicating that the interaction has biological relevance.…”
Section: Revolutamentioning
confidence: 99%
“…Chandler et al (2007) found that the HD-ZIPIII protein PHAVOLUTA interacts with the AP2 family DORNRÖ SCHEN and DORNRÖ SCHEN-LIKE transcription factors. Moreover, dornröschen dornröschenlike double mutants fail to make cotyledons indicating that the interaction has biological relevance.…”
Section: Revolutamentioning
confidence: 99%
“…The single mutants dornroschen (drn) and dornoschen-like (drnl) display a variety of cotyledon defects such as single or fused cotyledons, some aberrant divisions in the embryo and in rare instances a phenotype similar to mp (Chandler et al, 2007). Mutant drn embryos are also disturbed in auxin responsiveness (Chandler et al, 2007).…”
Section: Formation Of the Embryo Axismentioning
confidence: 99%
“…Mutant drn embryos are also disturbed in auxin responsiveness (Chandler et al, 2007). In a double mutant combining a strong drn allele with a weak drnl, the penetrance of all three phenotypes is greatly increased, whereas a homozygous double mutant combining a strong drn allele and a strong drnl allele shows a pinlike phenotype (Chandler et al, 2007).…”
Section: Formation Of the Embryo Axismentioning
confidence: 99%
See 2 more Smart Citations